Cerebrospinal fluid proteomic profiling in nusinersen‐treated patients with spinal muscular atrophy. Issue 5 (19th February 2020) - Kessler, Tobias; Latzer, Pauline; Schmid, Dominic; Warnken, Uwe; Saffari, Afshin; Ziegler, Andreas; Kollmer, Jennifer; Möhlenbruch, Markus; Ulfert, Christian; Herweh, Christian; Wildemann, Brigitte; Wick, Wolfgang; et al.
Abstract: Promising results from recent clinical trials on the approved antisense oligonucleotide nusinersen in pediatric patients with 5q‐linked spinal muscular atrophy (SMA) still have to be confirmed in adult patients but are hindered by a lack of sensitive biomarkers that indicate an early therapeutic response. Changes in the overall neurochemical composition of cerebrospinal fluid (CSF) under therapy may yield additive diagnostic and predictive information. With this prospective proof‐of‐concept and feasibility study, we evaluated non‐targeted CSF proteomic profiles by mass spectrometry along with basic CSF parameters of 10 adult patients with SMA types 2 or 3 before and after 10 months of nusinersen therapy, in comparison with 10 age‐ and gender‐matched controls. These data were analyzed by bioinformatics and correlated with clinical outcomes assessed by the Hammersmith Functional Rating Scale Expanded (HFMSE). CSF proteomic profiles of SMA patients differed from controls. Two groups of SMA patients were identified based on unsupervised clustering. These groups differed in age and expression of proteins related to neurodegeneration and neuroregeneration. Intraindividual CSF differences in response to nusinersen treatment varied between patients who clinically improved and those who did not. Data are available via ProteomeXchange with identifier PXD016757. Comparative CSF proteomic analysis in adult SMA patients before and after treatment with nusinersen‐identified subgroups and treatment‐related changes and may therefore be suitable for diagnostic and predictive analyses. Abstract : The approved antisense oligonucleotide nusinersen demonstrated convincing clinical results in patients with 5q‐linked spinal muscular atrophy (SMA) but predictive biomarkers are lacking to date. We evaluated cerebrospinal fluid (CSF) proteomic profiles by mass spectrometry from 10 adult patients with SMA types 2 or 3 before and after nusinersen treatment compared with matched healthy controls. We identified two clusters of different proteomic profiles related to neurodegeneration and neuroregeneration, and intraindividual treatment‐related changes varying between patients who clinically improved and those who did not. We think that CSF proteomic profiling according to our protocol is suitable for diagnostic and predictive analyses. Read the Editorial Highlight for this article on page 545 .